Removal of heavy metals using sorbents and biochemical indexes in rats - M. Ahmadi; I. Kalinin; V. Tomchuk (Ukrainian Journal of Veterinary Sciences, 2023)
A wide range of negative effects of heavy metals on the body of mammals predetermined the relevance of the search for ways to reduce the toxic effects of these chemical compounds. Solving this problem is possible by using sorbents. The research aims to determine the effect of sorbents on the content of heavy metals (cadmium, copper, lead, and zinc) in the rat tissues. Toxicological, physicochemical, and biochemical methods were used. Phillipsite sorbent reduced the content of copper and zinc in the blood of rats by 1.6 times, cadmium by 2 times and lead by 2.6 times. The content of copper and zinc in rat livers decreased by 1.4 times, and cadmium and lead – by 2 times. The content of the studied metals in kidney tissues decreased by half. A similar decrease in the level in the tissues was noted when using the chabazite sorbent for all heavy metals studied. Administration of the clinoptilolite sorbent into the body of rats contributed to a 2-fold decrease in the blood content of copper and zinc, cadmium, and lead by 2.6 and 3 times, respectively. A 1.6-fold decrease in copper and zinc levels and a 3-fold decrease in cadmium and lead levels were detected in the liver tissues. When mordenite sorbent was administered to animals, the content of copper and zinc in the blood decreased by 1.5 times, and cadmium and lead by 3 times compared to the control. The content of all studied metals in the liver of rats decreased by 2.4 times. The use of these sorbents in animal husbandry will contribute to the reduction of the content of heavy metals in animal tissues, which will ensure the production of high-quality and safe products, as well as contribute to the preservation of human health